Herramientas LMS como estrategia didáctica virtual para mejorar el rendimiento académico en los estudiantes de la Escuela de Educación Básica Federico Gonzales Suarez, Montalvo - Tapia Ochoa, Whitney Oswaldo (2022)
LMS tools today have become a set of very important digital resources that facilitate distance education and teaching-learning processes. These educational management resources allow the creation of innovative learning scenarios through the use of information and communication technologies, so that students and teachers can interact with each other in real time and from anywhere in the world. The objective of this research was to evaluate the way in which LMS tools improve the academic performance of students at the "Federico González Suarez" School of Basic Education, Montalvo. The study is structured under a non-experimental design; the types of research were descriptive, causal-cross-sectional and documentary. In addition, the methods used are: inductive and deductive. For the collection of information, a survey of students, an interview with teachers and an observation sheet were used as techniques. The results of the research show that students have a positive perception regarding the use of virtual learning tools, most of them expressed the benefits they generate such as: facilitates and encourages learning, the training process is innovative, improves teacher communication and increases academic performance. It is concluded that learning management tools (LMS) are very important because they contribute significantly to improving the teaching-learning process and promote the academic performance of students.